If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 83 + -1v = 274 Solving 83 + -1v = 274 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-83' to each side of the equation. 83 + -83 + -1v = 274 + -83 Combine like terms: 83 + -83 = 0 0 + -1v = 274 + -83 -1v = 274 + -83 Combine like terms: 274 + -83 = 191 -1v = 191 Divide each side by '-1'. v = -191 Simplifying v = -191
| 8.2x-57.4=-24.6 | | 10v+5v=25 | | 15n-25n+8n=18 | | 4g-13=3 | | 3(4z+9)=20-7z | | 24-c=2(3) | | 8y-5y=-27 | | -12n-12=-11n | | (-4v+3)(8v+6)=0 | | 9400=10 | | 9y-4y-14=48.80 | | 8.2x-53.4=-24.6 | | (t)=4t+3t^3+2t-7 | | -28-3n=8+6n | | X/5=33 | | 4v-13=59 | | 7b+8=4b-10 | | 4x+24=17 | | 54c+45d= | | 0=1-3sin(3x) | | 53=28-5(x-1) | | p-2.50=4a+10 | | X+45=77 | | 9x+3-3=0 | | 3x*-5x+2=0 | | 0.1x+.7=3.5 | | 21345/15 | | 4+8(1-9b)=-34 | | X-84=123 | | 0.9=0.3b | | 0.3(3z+7)+4.5=0.4(3z-6) | | 0.4x=2.6 |